Changes in Species Richness and Composition of Tiger Moths (Lepidoptera: Erebidae: Arctiinae) among Three Neotropical Ecoregions - Beccacece, Hernán Mario (2016)
Paraná, Yungas and Chaco Serrano ecoregions are among the most species-richterrestrial habitats at higher latitude. However, the information for tiger moths, one of the most speciose group of moths, is unknown in these ecoregion. In this study, we assess the species richness and composition on these three ecoregion. Also we investigated whether tiger moths species composition is influenced by climatic factors and altitude. Tiger moths species were obtained with samples from 71 sites using standardized protocols (21 sites were in Yungas, 19 in Paraná and 31 in Chaco Serrano). Rarefaction-extrapolation curves, non-parametric estimators for incidence and sample coverage indices were performed to assess species richness in the ecoregions studied. Non metric multidimensional scaling and adonis test were performed to compare the species composition of tiger moths among ecoregions. Permutest analysis and Pearson correlation were used to evaluate the relationship among species composition and annual mean temperature, annual temperature range, annual precipitation, precipitation seasonality and altitude. Among ecoregions Paraná was the richest with 125 species, followed by Yungas with 63 species and Chaco Serrano with 24 species. Species composition differed among these ecoregions, although Yungas and Chaco Serrano were more similar than Paraná. Species composition was significantly influenced by climatic factors and altitude. This study showed that species richness and species composition of tiger moths differed among the three ecoregions assessed. Furthermore, not only climatic factors and altitude influence the species composition of tiger moths among ecoregions, but also climatic seasonality at higher latitude in Neotropical South America region becomes an important factor.